CFD-Based Thermohydrodynamic Analysis of Vegetable Oil Lubricants in Journal Bearings - Muchammad; Budi Setiyana; Agus Suprihanto; Achmad Widodo (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
This study investigates the thermohydrodynamic performance of journal bearings lubricated with palm trimethylolpropane (TMP) ester as a biolubricant, compared to conventional engine oil, using computational fluid dynamics (CFD) in ANSYS Fluent. The objective is to evaluate the influence of lubricant type on pressure distribution, load carrying capacity, friction force, and cavitation behavior. The results show that palm TMP ester generates higher hydrodynamic pressure while maintaining a similar pressure distribution pattern to engine oil. The load carrying capacity increases significantly by approximately 493% at 48 rad/s and 343% at 68 rad/s compared to engine oil. However, this improvement is accompanied by an increase in friction force of about 280% and 234% at the respective speeds due to higher viscosity. In addition, the vapor volume fraction ranges from 0.69 to 0.73, indicating cavitation, with palm TMP ester showing a slightly higher tendency. These findings demonstrate a trade-off between enhanced load support and increased friction, highlighting the potential of palm TMP ester as an environmentally friendly lubricant for hydrodynamic bearing applications.